Terminal modulation of asymmetrical D−A−D−π furan-containing diketopyrrolopyrrole chromophores for intramolecular charge transfer properties. (June 2020) - Tao, Tao; Zhao, Jiongguang; Fan, Ben; Chen, Zelin; Sun, Jinwei
Abstract: Three furan-based diketopyrrolopyrrole (DPP) chromophores have the same D−A−D structure and various tetraphenylethylene, pyrene and dibenzothiophene tails with intramolecular donor-acceptor spacers. Different π -extended chromophores show different intramolecular charge transfer properties. Furthermore, according to UV–Vis and emission spectral studies, dyes F1 –F3 exhibit aggregation-caused quenching (ACQ) in tetrahydrofuran aqueous solutions. Interestingly, dyes F1 and F3 show aggregation-induced emission (AIE) behaviors in DMSO/toluene mixtures, while pyrene-functionalized DPP dye F2 still has ACQ character. It is noted that a contour plot is firstly carried out to be better understood the AIE and ACQ phenomena. Moreover, the energy gaps for the methyl counterpart of dyes F1 –F3 are 2.30, 2.29 and 2.35 eV, respectively, which indicate that introducing asymmetrical D−A−D− π furan-containing DPP structures can reduce the HOMO–LUMO gaps easily and rapidly. In addition, a computational and experimental investigation has been provided, including theoretical and optical energy gaps for full comparison. Graphical abstract: Image 1 Highlights: A contour plot is firstly demonstrated to be understood AIE and ACQ phenomena. Three asymmetrical D−A−D− π furan-based DPPs have been constructed. The fluorescence quantum yield of dye F1 is 49%, showing the strong peaks. A computational and experimental investigation has been provided.